Between Home’s Embrace and Laughter with Friends: Relationships that Shape Adolescent Happiness in a Systematic Literature Review - Hevitriana, Hevitriana; Ariyani, Mira; Deasyanti, Deasyanti (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
Adolescence is a crucial developmental period marked by significant social and emotional changes. This study aims to systematically examine the synergy between family and peer relationships in shaping adolescent well-being. The study was conducted using the Systematic Literature Review (SLR) method based on the PRISMA 2020 guidelines. The literature search was performed across five major databases (Scopus, JSTOR, PubMed, ProQuest, and Google Scholar) with a publication range of 2016–2025. Out of 1,001 identified articles, 22 studies met the inclusion criteria. The extracted data were then analyzed through a narrative-comparative approach, followed by a thematic synthesis to identify the contribution patterns of parental and peer relations to adolescent happiness. The synthesis results indicate that parental relationships are a strong predictor of long-term emotional stability and well-being. Conversely, peer relationships play a vital role in daily happiness and social relatedness. These two relations complement each other through synergy and compensation mechanisms, where family support provides a stable affective foundation, while peer support enriches social experience. These findings confirm that adolescent well-being is influenced by the quality of interpersonal relations within a broader socio-cultural context and provides a basis for developing holistic, relationship-based interventions.Masa remaja merupakan periode perkembangan yang krusial yang ditandai oleh perubahan sosial dan emosional yang signifikan. Penelitian ini bertujuan menelaah secara sistematis sinergi antara hubungan keluarga dan teman sebaya dalam membentuk kebahagiaan remaja. Kajian ini menggunakan metode Systematic Literature Review (SLR) berdasarkan panduan PRISMA 2020. Pencarian literatur dilakukan melalui lima basis data utama (Scopus, JSTOR, PubMed, ProQuest, dan Google Scholar) dengan rentang tahun publikasi 2016–2025. Dari 1.001 artikel yang teridentifikasi, sebanyak 22 studi memenuhi kriteria inklusi. Data kemudian dianalisis secara naratif-komparatif, dilanjutkan dengan sintesis tematik untuk mengidentifikasi pola kontribusi relasi terhadap kebahagiaan remaja. Hasil sintesis menunjukkan bahwa hubungan dengan orang tua merupakan prediktor kuat kebahagiaan dan stabilitas emosional jangka panjang. Sementara itu, hubungan dengan teman sebaya berperan penting dalam kebahagiaan harian dan keterhubungan sosial. Kedua relasi tersebut saling melengkapi melalui mekanisme sinergi dan kompensasi, di mana dukungan keluarga menyediakan fondasi afektif yang stabil, sedangkan dukungan teman sebaya memperkaya pengalaman sosial. Temuan ini menegaskan bahwa kesejahteraan remaja dipengaruhi oleh kualitas relasi interpersonal dalam konteks sosial-budaya yang lebih luas dan menjadi dasar bagi pengembangan intervensi berbasis relasi yang holistik.